2019
DOI: 10.1080/14763141.2018.1553244
|View full text |Cite
|
Sign up to set email alerts
|

Test-retest reliability of segment kinetic energy measures in the golf swing

Abstract: OUTRAM, Tom and WHEAT, Jonathan (2019). Test-retest reliability of segment kinetic energy measures in the golf swing. Sports Biomechanics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 42 publications
(69 reference statements)
1
7
0
Order By: Relevance
“…This hypothesis was confirmed by our results, since seven to ten trials were required to reliably measure swing performance in high-handicap players. These numbers of trials were higher than those recommended for low-handicap players (i.e., three to five trials) [ 5 , 6 , 7 , 8 , 10 , 20 ] and similar to those found for medium-handicap players (i.e., ten trials) [ 9 ]. Finally, Severin et al recommended between 4 and 12 trials for low-handicap players to measure kinematic and kinetic variables during swing performance [ 22 ].…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations
“…This hypothesis was confirmed by our results, since seven to ten trials were required to reliably measure swing performance in high-handicap players. These numbers of trials were higher than those recommended for low-handicap players (i.e., three to five trials) [ 5 , 6 , 7 , 8 , 10 , 20 ] and similar to those found for medium-handicap players (i.e., ten trials) [ 9 ]. Finally, Severin et al recommended between 4 and 12 trials for low-handicap players to measure kinematic and kinetic variables during swing performance [ 22 ].…”
Section: Discussionsupporting
confidence: 51%
“…For example, although carry distance could be measured with a single swing for the six iron according to the ICC value (i.e., 0.88), the MDC varied from 31.53 m for one trial to 17.97 m for the mean value of six trials. This study recommends more trials than the five trials used by Outram and Wheat in their reliability study [ 20 ]. These differences could have been due to the disparity in the skill levels between the golfers in the two studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The athlete's contribution was measured by two studies varying either club choice or the athlete's experience. Outram and Wheat, using similar IMU technology to measure the total work required to swing the club, varied between 223 to 269 joules depending on the club used [19]. Nesbit and Serrano used a computer model of 4 different golfers with varying handicaps and work varied between 235 and 355 Nm with the higher work observed with the scratch golfer [20].…”
Section: Hitting the Golf Ballmentioning
confidence: 99%